Penicillium expansum versus antagonist yeasts and patulin degradation in vitro - Coelho, Alexandre Rodrigo; Celli, Marcos Giovani; Ono, Elisabete Yurie Sataque; Wosiacki, Gilvan; Hoffmann, Fernando Leite [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Hirooka, Elisa Yoko (Brazilian Archives of Biology and Technology, 2007)
Considerando o antagonismo e degradação de patulina detectados em Pichia membranifaciens e Sporobolomyces roseus no estudo preliminar, este trabalho avaliou o efeito antagônico de Pichia ohmeri 158 no desenvolvimento de Penicillium expansum e a degradação de patulina in vitro. O sobrenadante do cultivo de P. ohmeri 158 inibiu 66,17% do desenvolvimento micelial, indicando antibiose relacionada ao fator killer. A concentração inicial de patulina (223 µg) na presença de células íntegras de P. ohmeri foi reduzida em mais de 83% após dois dias de incubação a 25ºC e superior a 99% após 5 dias, com níveis indetectáveis no 15º dia. O decréscimo do pH 4,0 inicial para pH 3,3 sugeriu que a eliminação de patulina é um processo ativo e uma conseqüência do metabolismo da levedura. Os resultados obtidos concluem que P. ohmeri 158 é uma alternativa promissora na inibição do desenvolvimento de P. expansum e na degradação de patulina.

Taking into account the preliminary antagonistic/biodegradation property showed by Pichia membranifaciens and Sporobolomyces roseus, which decreased the initial patulin concentration of 588.4 to 290.0 µg/mL, ability of P. ohmeri 158 in biocontrol against Penicillium expansum and patulin decrease in vitro was performed. The culture supernatant of P. ohmeri 158 was effective against 66.17% micelial growth, indicating antibiosis related with the killer phenomenon. The initial patulin concentration of 223 µg in the presence of P. ohmeri 158 cells was decreased over 83% of the original concentration, when incubated at 25ºC/2 days and > 99% after 5 days incubation time, with undetectable patulin level after 15 days. The initial pH 4.0 decreased to pH 3.3 along 15 days experiment, suggesting that patulin decrease was an active process and a consequence of yeast metabolism. The results suggested that P. ohmeri 158 could be a promising alternative for the inhibition of P. expansum growth and patulin degradation.
Keywords: Penicillium expansum; antagonist yeasts; biocontrol; Patulin; degradation